Tawar Suku Kutai di Kabupaten Kutai Kartanegara Ditinjau dari Bentuk Mantra, Aspek Budaya, dan Fungsi - Arifin, Syaiful; Resfilianda, Klarazetz Revina (Universitas Mulawarman, 2022)
The purpose of this study is to find out the form, cultural aspects, and functions contained in the Kutai Tribe's Tawar mantra. The method used is a method of content analysis and uses fishing techniques, interviews, recordings and introspection. The results of the research obtained by data in the form of (i) Mantra consists of several series of words that have elements of rhythm and rhyme; (ii) The content of the spell relates to supernatural powers; (iii) Contain words of seduction, challenge, command and curse; (iv) Having selected words that are considered powerful or have supernatural powers; (v) Have a tradition of bargaining; (vi) Have a function in its society; (vii) Use of media in the treatment process. The cultural aspect that exists in traditional medicine is to form like a cross when doing the treatment process in the sick sufferer depending on the pain suffered and treatment at the time of sun. Kutai tribe treatment mantra based on the results of analysis of its bargain function possessed by the Kutai Tribe in accordance with the purpose and function of the mantra, namely (i) to obtain power from God (ii) to rule, persuade, curse or expel evil spirits and treat the sick.